Nonlinear finite element analysis of spar platform - Jameel, A.B.M.M.; Islam, S.; Khaleel, M.; Jumaat, Mohd Zamin (Advanced Science Letters, 2012)
In recent decades, oil and gas exploration technology has moved towards the offshore deep-water deposits. Conventional fixed jacket type platforms and bottom supported compliant platforms are found to be inefficient for exploring these resources. Floating Spar platform is suitable alternative in deep water regions. The present study performs coupled analysis of integrated Spar platform with full hull cylinder. This mathematical model incorporates almost all the major nonlinearities. Time domain analysis is done adopting an automatic Newmark- Î² time integration technique. Airy's wave theory is used for calculating for wave kinematics. Wave induced spar hull motion in surge, heave and pitch directions along with maximum tension in mooring line has been assessed for extreme wave height condition in 1018 m water depth.